2017
DOI: 10.1007/s10344-017-1144-z
|View full text |Cite
|
Sign up to set email alerts
|

Attractants for wild pigs: current use, availability, needs, and future potential

Abstract: Populations of wild pigs (Sus scrofa) are burgeoning around the globe, and they are currently the target of extensive research and management efforts. Wild pigs are a highly successful invasive species that cause extensive damage to agriculture and native plant and animal communities. Lethal control is the most common management strategy used to reduce wild pig populations and their damage, and many lethal strategies rely on luring wild pigs to a specific location. Most commonly, a food commodity such as corn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 113 publications
0
22
0
Order By: Relevance
“…As omnivores, wild pigs feed on whatever resources are present (Mayer and Brisbin , Lavelle et al. ), but their population dynamics can be strongly influenced by pulsed resources (i.e., mast seeding; Bieber and Ruf ) motivating our prediction that the agricultural functional response in wild pigs would change as non‐agricultural resources became more available. Similarly, we found that, as non‐agricultural forage resources became more abundant within a wild pig's core home range, the agricultural functional response in terms of monthly crop use decreased disproportionately more in areas with high crop availability relative to areas with low crop availability.…”
Section: Discussionmentioning
confidence: 99%
“…As omnivores, wild pigs feed on whatever resources are present (Mayer and Brisbin , Lavelle et al. ), but their population dynamics can be strongly influenced by pulsed resources (i.e., mast seeding; Bieber and Ruf ) motivating our prediction that the agricultural functional response in wild pigs would change as non‐agricultural resources became more available. Similarly, we found that, as non‐agricultural forage resources became more abundant within a wild pig's core home range, the agricultural functional response in terms of monthly crop use decreased disproportionately more in areas with high crop availability relative to areas with low crop availability.…”
Section: Discussionmentioning
confidence: 99%
“…A second reason for a decrease in CPUE from trapping could be that, since the start of the NFSP, there has been a large influx of less experienced trappers, and trapping work has expanded into new habitats where trapping techniques, including baits and lures, have not yet been optimized. For example, the attractiveness of specific baits can be relative to other local resources (Lavelle et al 2017). Trapping efficiency could likely be improved in areas where feral swine are rare or where baits are less effective by investing research in new baits and lures that are intensely attractive over a variety of ecological conditions (Lavelle et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the attractiveness of specific baits can be relative to other local resources (Lavelle et al 2017). Trapping efficiency could likely be improved in areas where feral swine are rare or where baits are less effective by investing research in new baits and lures that are intensely attractive over a variety of ecological conditions (Lavelle et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Baiting of wild animals has positive and negative attributes for wildlife management and control. Baiting can increase efficacy of population control activities by attracting the pest species across broad landscapes (Lavelle et al, 2017). However despite this increased removal, baiting also generates unwanted conditions such as concentrating animals, increasing contact and spread of diseases, increasing fecundity, habituating wild animals to humans, and more (Dunkley and Cattet, 2003;The Wildlife Society, 2007;Sorensen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Baiting is one of the most commonly used methods for applying control methods for wild pigs, or monitoring populations of wild pigs (Mayer and Brisbin, 2009;Engeman et al, 2013;Bengsen et al, 2014;Lavelle et al, 2017). Typically, baits stimulate both smell and taste for wild pigs, and provide sustenance (Lavelle et al, 2017).…”
Section: Introductionmentioning
confidence: 99%